Mobility and settlement dynamics of Large Cutting Tool makers in the subtropical forests of South China: A simulated ecological approach. (April 2022) - Li, Hao; Zhang, Meng; Lotter, Matt G.; Lei, Lei; Li, Dawei; Kuman, Kathleen
Highlights: Simulated environmental variables and technological attributes are employed. Short travel distances and small ranging territories were preferred strategies. Site occupation and/or settlement was likely temporary in nature. Lifeways of hominids within humid subtropical forests are better understood. Abstract: New research in recent years has enriched our understanding of the spatio-temporal distribution of Large Cutting Tool (LCT) technology in Paleolithic China. Yet, few studies have focused on hominid social behaviors, and by analyzing LCTs from the Baise Basin in southern China, this case study aims to clarify some of these strategies for the region. Specifically, by employing two primary lines of evidence that consider both quantitative environmental variables and technological tool attributes, the results suggest that hominids preferred to adopt behavioral strategies associated with short-distance travelling and small-territory ranging. Furthermore, given the low density of stone artifacts and LCTs in all excavated sites, the somewhat homogenous landscape, and the even distribution of plant-dominated resources throughout the basin, site occupation and/or settlement was likely temporary in nature. Overall, the use of ecological simulations and analogous approaches in this study provides a series of new data for understanding lifeways of early humans in the humid subtropical forests of South China, and equally important, promote new research avenues for understanding the dynamics of the Chinese Paleolithic.